Experimental study on impact dynamic characteristics of bolted rock specimens - WANG Xiaoqing (矿业科学学报)
In order to study the impact dynamic characteristics of bolted rock mass under dynamic loads, dynamic tests with different impact pressures were carried out on bolted and unbolted specimens using the SHPB test system. The stress wave propagation characteristics, stress-strain relationship, energy evolution and failure modes of the specimens were compared and analyzed. The reinforcement effect of rockbolts on rock mass under dynamic loads was verified and the reinforcement mechanism of rockbolts was obtained. The results show that: (1) Under the same impact pressure, the transmission-wave amplitude and transmission energy of bolted specimens are greater than those of unbolted specimens. The dissipated energy of bolted specimens is always lower than that of unbolted specimens. As the impact pressure increases, the dissipated energy of the two types of specimens gradually increases, but the difference in dissipated energy gradually decreases. (2) The dynamic peak stress and peak strain of both bolted and unbolted specimens increase with the impact pressure, showing a significant strain rate effect. (3) The rockbolt pretension generates a compressive stress field inside the specimen, forming a conical reinforcement core surrounding the rockbolt. Under the same impact pressure, the fragmentation degree of bolted specimens is significantly lower than that of unbolted specimens.